KLASIFIKASI DAN KELIMPAHAN BENTHOS BERDASARKAN KARAKTERISTIK HABITAT MANGROVE DI TELUK PANGPANG TAMAN NASIONAL ALAS PURWO - , NINDA ASMARANI KARNINGSIH, S.HUT; , Dr. Erny Poedjirahajoe, MP ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mangrove forests in the Alas Purwo National Park is still natural and unique. Mangrove forests are ecosystems that have high productivity and rich of nutrient. Mangroves provide an important role for aquatic ecosystems through the falling litters as organic material. Falling leaves of the mangrove is the main source of nutrients and energy that is very productive. Mangrove leaf decomposition process conducted by benthos organisms. The resulting detritus is not just the basis of formation of mangrove ecosystem's food chain, but rather as a source of food and nutrients for biota in the environment surrounding waters. The importance of the role of the benthos as a primary decomposer on mangrove ecosystems so much needed classification of benthos. Classification of benthos needed to simplify density and its functions so that it is easier to learn. This main objective of the research was to classify the mangrove habitat characteristics based on benthos and know the main parameter influencing the clasification of benthos. The research was conducted on each the ecological units that had been formed. Data retrieval is performed using the method transek plot line. To meet these objectives is done in the form of data retrieval of physical factors of biological chemistry water and vegetation density. Manufacture of benthos classification using cluster analysis and to determine the main factors influencing the classification by using discriminant analysis. Based on the research results obtained are 2 classification is A group (for ecological units 1.4.5 and 6) and group B (for ecological units 2.3 and 7). The group of A has a high diversity of benthos and condition of the habitat is better than group B. The main parameters that affect the classification of the benthos is vegetation density. Because vegetation density to influence of litters productivity that to used benthos organism to decomposed being nutrient to mangrove ecosystem.